Assessment of Energy Efficiency Measures on Indoor Air Quality and Microclimate in Buildings of Liepaja Municipality. (September 2016) - Asere, Liva; Mols, Toms; Blumberga, Andra
Abstract: Eight municipality buildings that have undergone major energy efficiency improvements have been studied. The main aim is to assess indoor air quality and microclimate in the context of energy efficiency, indoor air quality and thermal comfort dilemma in the studied buildings. Microclimate and CO2 measurements were carried out. Tracer gas method was used to determine air exchange rate and blower door tests were conducted to determine building tightness. Results show that ventilation systems are underperforming because they are not used as expected, thus leading to decreased indoor air quality and thermal comfort. Further assessment of economic aspects would be necessary to evaluate the indoor air quality impact on student and teacher health and productivity and its impact on municipality budgets.